Kepuasan Akseptor KB Implan di Puskesmas Ma’rang Kabupaten Pangkep - Frida Yuanita; Mar'atussaliha Mar'atussaliha; Putri Putri (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Acceptor satisfaction is an expression of feelings that arise as a result of the performance of health services obtained after the acceptor compares the services received with what he expected, while patient dissatisfaction arises because of the discrepancy between the patient's expectations and the performance of the health services received when using health services. The purpose of this study was to determine the relationship between physical evidence, responsiveness and assurance with the satisfaction of implant acceptors at the Ma'rang Health Center. This research is a quantitative study with a cross-sectional design using sampling data, namely using total sampling with a total sample of 78 acceptors. Data analysis in this study used the Chi-Square Test. The results of this study indicate that there is a relationship between physical evidence and the satisfaction of implant acceptors at Ma'rang Health Center with a p-value of 0.040, there is a relationship between responsiveness and satisfaction of implant acceptors at Ma'rang Health Center with a p-value of 0.041, and there is a relationship between assurance and satisfaction of implant acceptors at the Ma'rang Health Center with a p-value of 0.047.